2005
DOI: 10.1152/ajplung.00101.2004
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 is essential for maximal neutrophil recruitment and methacholine responsiveness after ozone exposure

Abstract: Shore. CXCR2 is essential for maximal neutrophil recruitment and methacholine responsiveness after ozone exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 67 publications
(83 reference statements)
8
104
0
Order By: Relevance
“…On the contrary, we observed that APAP-induced liver injury was markedly attenuated in CXCR2-KO mice with reduced neutrophil infiltration, compared with WT mice, in line with previous reports that CXCR2-KO mice exhibited attenuated neutrophil infiltration in various disease models [16][17][18][19][20][21][22][23][24][25][26][27]. Indeed, Hogaboam and colleagues [38] observed that only a low level of CXCR2 was expressed on untreated hepatocytes and that APAP could enhance CXCR2 protein expression only transiently with a time lag.…”
Section: The Roles Of Ho-1 In Apap-induced Liver Injurysupporting
confidence: 91%
See 1 more Smart Citation
“…On the contrary, we observed that APAP-induced liver injury was markedly attenuated in CXCR2-KO mice with reduced neutrophil infiltration, compared with WT mice, in line with previous reports that CXCR2-KO mice exhibited attenuated neutrophil infiltration in various disease models [16][17][18][19][20][21][22][23][24][25][26][27]. Indeed, Hogaboam and colleagues [38] observed that only a low level of CXCR2 was expressed on untreated hepatocytes and that APAP could enhance CXCR2 protein expression only transiently with a time lag.…”
Section: The Roles Of Ho-1 In Apap-induced Liver Injurysupporting
confidence: 91%
“…Several lines of evidence demonstrated that the recruitment of neutrophils was significantly reduced in some disease models using mice lacking CXC chemokine receptor 2 (CXCR2), a receptor for CXCL1 and CXCL2 [19][20][21][22][23][24][25][26]. Our previous study demonstrated that the magnitude of liver injury induced by APAP well correlated with intrahepatic neutrophil number and intrahepatic myeloperoxidase activity, suggesting that neutrophil recruitment was involved in the pathogenesis of APAP-induced liver injury [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…KC and MIP-2 are sufficient to induce neutrophil recruitment, and they are necessary in many types of pulmonary inflammation (3,42,43). The present results demonstrate that TNFR and IL-1R are essential to the expression of KC and MIP-2 during pneumococcal pneumonia.…”
Section: Discussionmentioning
confidence: 52%
“…We hypothesized that higher doses of LPS must have caused productions of neutrophil chemoattractants to induce neutrophil recruitment. MIP-2 and KC are chemoattractants for neutrophil recruitment, MIP-2 has been reported previously to mediate neutrophil recruitment into lung in response to LPS (23). Level of MIP-2 ( Fig.…”
Section: Direct Endothelium Activation Was Sufficient For Neutrophil mentioning
confidence: 85%